The invasive snail Lissachatina fulica (Mollusca: Achatinidae): Its population structure in an area of recent colonization in Argentina - Valente, Romina (2020)
The giant African snail Lissachatina fulica is an invasive mollusk native to Africa. The first record of this snail in Argentina was in Puerto Iguazú, in 2010. Lissachatina fulica cause severe impacts as displaces native fauna and produce considerable damage to agricultural systems. For this reasons, it is recognized as one of the world’s most damaging pests listed in the Global Invasive Species Database. The objective of this work was to know the population structure of L. fulica in function of time and environmental variables in order to analyze and evaluate the establishment of the giant African snail population in Puerto Iguazú, Argentina, an area of recent colonization. The snail shells were measured and separated into four equal size ranges. The results showed that the smaller size (0-3cm) is more represented in the dry season and the intermediate sizes (3-6 and 6-9 cm) in the wet season. The body growth and biomass in L. fulica is influenced by environmental factors. This result indicates that L. fulica populations are already established in Puerto Iguazú, showing the importance of incorporate management programs and control strategies of this pest.